A Thermo-Poro-Viscoelastic Model for the Behavior of Polymeric Porous Separators. (24th August 2017) - Behrou, Reza
Abstract : This paper presents a continuum formulation for thermo-viscoelastic behavior of fully saturated porous media. Two-phase mixture with solid and fluid phases is considered. Governing and balance equations of the mixture, including the balance of mass, balance of linear momentum and balance of energy are presented. The displacement of the solid skeleton, pore fluid pressure, and temperature of the mixture are considered as independent state variables. The stress-strain relationship of the solid skeleton is described by a linear viscoelastic model. The fluid flow is described by the Darcy's law. Numerical examples are presented to show the performance of the model.